Collaborative Governance dalam Penanggulangan Potensi Banjir di Kota Malang (Studi pada Badan Penanggulangan Bencana Daerah Kota Malang) - Ardiansyah, Feri Achmad; Hayat, Hayat; Ilyas, Taufiq Rahman (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2024)
This research discusses the role of Collaborative Governance in overcoming potential floods in Malang City. This research is motivated by the many flooding problems in several points in Malang City that have not been resolved. The aim of this research is to examine the role of Collaborative Governance in flood management in Malang City. The method used in this research is qualitative method. The informants in this research were the Regional Disaster Management Agency and the surrounding community. The results of this research show that the duties and responsibilities of the Regional Disaster Management Agency in dealing with disasters are quite good. On the other hand, the research results found that the factors that cause flooding are not only natural factors but also a lack of public concern for the environment. Apart from that, existing obstacles to flood management are also due to limited funds, lack of public awareness, and the existence of sectoral egos.